The Stability of TSH, and Thyroid Hormones, in Patients Treated With Tablet, or Liquid Levo-Thyroxine - Antonelli, Alessandro; Elia, Giusy; Ragusa, Francesca; Paparo, Sabrina Rosaria; Cavallini, Gabriella; Benvenga, Salvatore; Ferrari, Silvia Martina; Fallahi, Poupak (Frontiers in Endocrinology, 2021)
Approximately, 5% of the population is affected by hypothyroidism, mainly women and persons aged more than 60 years. After the diagnosis of hypothyroidism the usual therapy is tablet levothyroxine (L-T4), with a monitoring of the thyroid-stimulating hormone (TSH) level in primary hypothyroidism every 6–8 weeks and L-T4 is adjusted as necessary to reach an euthyroid state. Once TSH is stabilized in the normal range, it is recommended to conduct annual testing in the treated subjects to warrant suitable replacement. More recently advances regarding L-T4 treatment are the introduction of new oral formulations: the liquid solution, and soft gel capsule. The soft gel capsule permits a quick dissolution in the acid gastric pH. The liquid preparation does not require an acid gastric environment. Many pharmacokinetic studies demonstrated a more rapid absorption for the liquid L-T4, or capsule, than with tablet. Many studies have shown that the liquid, or capsule, formulations can overcome the interaction with foods, drugs or malabsorptive conditions, that are able to impair the tablet L-T4 absorption. Lately studies have suggested that liquid L-T4 can permit to maintain more efficiently normal TSH levels in hypothyroid patients in the long-term follow-up, than tablet L-T4, both in patients with malabsorptive states, and in those without malabsorption. Further large, prospective, longitudinal studies are needed to evaluate the stability of TSH, in hypothyroid patients treated with different L-T4 formulations.